(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the indications for hysterectomy during and after childbirth and some related factors at Hanoi Obstetrics and Gynecology Hospital. Materials and methods: A descriptive cross-sectional study was conducted on 276 cases of postpartum hysterectomy performed at Hanoi Obstetrics and Gynecology Hospital from 2019 to 2023. Results: Over the 5-year study period, there were 276 cases of hysterectomy during and after childbirth. The main cause for hysterectomy was postpartum hemorrhage (98.1%), the most common indications were placenta accreta (68.1%), uterine atony (13.8%), and uterine fibroids (10.1%). The main indications for elective hysterectomy were placenta accreta and uterine fibroids. Emergency hysterectomy was primarily indicated for uterine atony, placenta previa, and uterine rupture. The primary conservative measures before performing hysterectomy during and after childbirth were hemostatic uterotonics (31.2%), uterine control (15.9%), and techniques such as uterine artery ligation and pelvic compression (12.7%), hemostatic sutures at the placental site (7.6%), and B-lynch sutures (4.7%). Conclusions: Hysterectomy during and after childbirth is a major surgery often performed to manage severe postpartum hemorrhage when conservative measures are ineffective, the most common causes are bleeding, specifically placenta accreta, uterine atony, and uterine fibroids.